Saccharomyces boulardii (CNCM I-745) improves intestinal damage in sepsis by remodeling intestinal flora structure - Liu, Hui-Ying; Li, Yao; Lin, Yi-Lu; Tang, Yu-Jia; Zhao, Jin-Da; Xu, Jia; Wang, Kuo; Zhi, Ying-Fei; Zhang, Yan; Deng, Jia-Le; Kang, Kai; Chen, Ying; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSepsis is one of the leading causes of mortality among intensive care unit (ICU) patients. The intestinal tract is the primary organ affected by sepsis, resulting in dysbiosis of the gut microbiota and negatively impacting long-term prognosis. This study investigated the protective effects of Saccharomyces boulardii (S. boulardii) on intestinal damage during sepsis.MethodsDistilled water was administered orally by intragastric for 4 weeks in control group and sepsis group. S. boulardii (CNCM I-745) suspension (108CFU/ml) was administered orally by intragastric for 4 weeks in probiotic group and treatment group. Rats in control group and probiotic group received the intraperitoneal injection of normal saline (5ml/kg). Rats in sepsis group and treatment group received the intraperitoneal injection of LPS solution (1mg/ml). Eight hours after the intraperitoneal injection, samples of serum, colonic tissue, and colonic contents were collected and stored at - 80°C. Four weeks later, the samples of colonic contents were taken to observe the alterations in the intestinal microbiota.ResultsSepsis led to an increase in the expression of IL-6, TNF-α, and a decrease in the expression of occludin. After treatment with S. boulardii (CNCM I-745), the inflammatory damage with sepsis was reduced, and the expression level of occludin was significantly increased. High-throughput sequencing analysis revealed that sepsis injury led to a decline in both the diversity and abundance of the gut microbiota. Simultaneously, the colonization of beneficial bacteria within the intestine diminished, whereas the colonization of harmful bacteria surged. However, upon administration of S. boulardii (CNCM I-745), an increase in the diversity and abundance of the gut microbiota was evident. Moreover, the composition of the gut microbiota underwent a discernible alteration.ConclusionSepsis induces impairment of intestinal barrier function and exacerbates inflammatory responses. The use of S. boulardii (CNCM I-745) can modulate the composition of the intestinal flora by enhancing the colonization of beneficial bacteria while reducing the presence of harmful bacteria. It helps maintain intestinal mucosal barrier function, mitigates intestinal damage associated with sepsis, and potentially influences the long-term growth and development of pediatric sepsis patients.